Conference Report: Drug discovery in the 21st century. (December 2011) - Pollastri, Michael P
The Advanced Pharmaceutical Chemistry conference entitled was held on 6–7 June 2011 at the Broad Institute in Cambridge, MA, USA. This 2-day conference focused on four specific areas: applying biophysical techniques to address current challenges in medicinal chemistry and drug discovery; treatment interventions for Alzheimer''s disease; drug discovery for orphan, rare and neglected diseases; and kinase drug discovery for chronic and rare diseases. The meeting attracted 80 attendees, approximately 95% of whom were drawn from the local biopharmaceutical industry.